Population genetics of fruit bat reservoir informs the dynamics, distribution and diversity of Nipah virus. Issue 5 (12th November 2019) - Olival, Kevin J.; Latinne, Alice; Islam, Ariful; Epstein, Jonathan H.; Hersch, Rebecca; Engstrand, Rachel C.; Gurley, Emily S.; Amato, George; Luby, Stephen P.; Daszak, Peter
Abstract: The structure and connectivity of wildlife host populations may influence zoonotic disease dynamics, evolution and therefore spillover risk to people. Fruit bats in the genus Pteropus, or flying foxes, are the primary natural reservoir for henipaviruses—a group of emerging paramyxoviruses that threaten livestock and public health. In Bangladesh, Pteropus medius is the reservoir for Nipah virus—and viral spillover has led to human fatalities nearly every year since 2001. Here, we use mitochondrial DNA and nuclear microsatellite markers to measure the population structure, demographic history and phylogeography of P. medius in Bangladesh. We combine this with a phylogeographic analysis of all known Nipah virus sequences and strains currently available to better inform the dynamics, distribution and evolutionary history of Nipah virus. We show that P. medius is primarily panmictic, but combined analysis of microsatellite and morphological data shows evidence for differentiation of two populations in eastern Bangladesh, corresponding to a divergent strain of Nipah virus also found in bats from eastern Bangladesh. Our demographic analyses indicate that a large, expanding population of flying foxes has existed in Bangladesh since the Late Pleistocene, coinciding with human population expansion in South Asia, suggesting repeated historical spillover of Nipah virus likely occurred. We present the first evidence of mitochondrial introgression, or hybridization, between P. medius and flying fox species found in South‐East Asia ( P. vampyrus and P. hypomelanus ), which may help to explain the distribution of Nipah virus strains across the region. Abstract : see also the Perspective by Carver et al